2013
DOI: 10.4236/aim.2013.31006
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ethanol Production by Combination of Recombinant <i>Ralstonia eutropha</i> and Electrochemical Reducing Power

Abstract: Ralstonia eutropha was genetically modified to induce ethanol production from glucose. An electrochemical bioreactor was prepared to generate electrochemical reducing power coupled to regeneration of NADH. Growing cells of recombinant R. eutropha produced about 29 mM of ethanol in conventional conditions and 56 mM of ethanol in electrochemically reduced conditions from 100 mM glucose. Grown cells of the recombinant produced about 52 mM of ethanol in conventional conditions and 142 mM of ethanol in electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Moreover, it was reported that PHB producing strains have the ability to balance the reducing equivalents generated from carbon metabolism by using PHB as a sink for reducing power (i.e., NADPH) [ 26 , 27 ]. Additionally, fermentative bacteria (grown on CO 2 and H 2 ) with high reducing power (NADH) favor metabolite production over cell growth [ 28 ]. In opposite to these expectations, the control experiments with introducing hydrogen did not show any PHB production.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was reported that PHB producing strains have the ability to balance the reducing equivalents generated from carbon metabolism by using PHB as a sink for reducing power (i.e., NADPH) [ 26 , 27 ]. Additionally, fermentative bacteria (grown on CO 2 and H 2 ) with high reducing power (NADH) favor metabolite production over cell growth [ 28 ]. In opposite to these expectations, the control experiments with introducing hydrogen did not show any PHB production.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, cathodically reduced neutral red has been shown to drive fumarate reduction in Actinobacillus succinogenes (Park and Zeikus, 1999), act as the sole electron donor for growth and metabolite formation (Park et al, 1999), generate a proton motive force in combination with a proton-translocating fumarate reductase (Park and Zeikus, 1999), chemically reduce NAD + (Park and Zeikus, 1999), enhance ethanol production in Clostridium thermocellum and Saccharomyces cerevisiae (Shin et al, 2002), enhance reduced pathway flux in Weissella kimchii (Park et al, 2005), modify carbon flow in Clostridium acetobutylicum (Girbal et al, 2006), and when immobilized on a graphite electrode, enhance ethanol formation in Zymomonas mobilis (Jeon et al, 2009; Jeon and Park, 2010) and Ralstonia Eutropha (Jeon et al, 2013). There is confusion from some of these reports where high voltage drops were involved, which may have produced hydrogen via electrolysis in addition to reducing neutral red.…”
Section: Introductionmentioning
confidence: 99%
“…There is confusion from some of these reports where high voltage drops were involved, which may have produced hydrogen via electrolysis in addition to reducing neutral red. Some of these voltage drops include: 2 V (Jeon et al, 2012), 3 V (Jeon et al, 2009, 2013), and 1-10 V variable (Jeon and Park, 2010; Shin et al, 2002). Very few studies employed the use of a potentiostat to monitor and control working electrode potential while simultaneously quantifying charge transfer in order to compare electron delivery with metabolite production, with at least one recent exception (Choi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Electricity generated from regenerative energies sources can be stored in form of electromicrobial fuels. Recombinant strains of R. eutropha were used electromicrobial conversion of CO2/formate to higher alcohols (47,65). These auto-and mixotrophical approaches comprise, on one hand, the possibility to store energy and on the other, consume CO2, which is also beneficial for the environment.…”
Section: Utilization Of C1-compoundsmentioning
confidence: 99%